2001
DOI: 10.1016/s0896-6273(01)00357-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin-Induced Transport of a β-Actin mRNP Complex Increases β-Actin Levels and Stimulates Growth Cone Motility

Abstract: Neurotrophin regulation of actin-dependent changes in growth cone motility may depend on the signaling of beta-actin mRNA transport. Formation of an RNP complex between the beta-actin mRNA zipcode sequence and Zipcode Binding Protein 1 (ZBP1) was required for its localization to growth cones. Antisense oligonucleotides to the zipcode inhibited formation of this RNP complex in vitro and the neurotrophin-induced localization of beta-actin mRNA and ZBP1 granules. Live cell imaging of neurons transfected with EGFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
359
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(385 citation statements)
references
References 56 publications
(12 reference statements)
22
359
2
1
Order By: Relevance
“…To date, a number of RNA binding and transport proteins have been localized to dendrites, but only one, ZBP1, has been conclusively localized to axons (Zhang et al, 2001). This scarcity of data on candidate proteins for RNA transport to axons presents an obstacle for understanding the role of intra-axonal protein synthesis, because, aside from ZBP1, many of the proteins thought to be involved in RNA localization have not been demonstrated there.…”
Section: Stau2 and Fmrp Proteins Localize To Drg Axons: Implications mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, a number of RNA binding and transport proteins have been localized to dendrites, but only one, ZBP1, has been conclusively localized to axons (Zhang et al, 2001). This scarcity of data on candidate proteins for RNA transport to axons presents an obstacle for understanding the role of intra-axonal protein synthesis, because, aside from ZBP1, many of the proteins thought to be involved in RNA localization have not been demonstrated there.…”
Section: Stau2 and Fmrp Proteins Localize To Drg Axons: Implications mentioning
confidence: 99%
“…To this end, various components of the translational machinery have been identified in the axons of DRG neurons (Koenig, 1991;Pannese and Ledda, 1991;Verma et al, 2005), and translation itself has been shown to occur in these axons (Koenig, 1991;Zheng et al, 2001;Verma et al, 2005;Willis et al, 2005). However, with the exception of zipcode binding protein 1 (ZBP1), which transports β-actin mRNA to growth cones (Zhang et al, 2001), RNA binding and transport molecules have not been shown to be present in axons, and none, to our knowledge, have been localized to the axons of DRG afferents.In this study, we tested the hypothesis that two of the best characterized RNA binding and transport proteins, staufen (stau) and fragile X mental retardation protein (FMRP), localize to extra-somal sites in sensory neurons, consistent with a role in RNA transport. Here, we provide evidence that DRG and TG neurons express a number of RNA binding and transport proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This localization can be induced by NT-3 signaling, or by cAMP elevation and subsequent PKA activation (Zhang et al 1999). This axonal distribution can be inhibited with antisense oligonucleotides that disrupt the binding of the actin mRNA to Zipcode Binding Protein (ZBP-1), which also blocked the NT-3-induced protein localization at the growth cone and decreased growth cone motility (Zhang et al 2001). Therefore trophic stimulation of axon growth may involve the stimulation of localized mRNA transport and protein synthesis as a mechanism of quickly localizing needed proteins.…”
Section: How Do Extracellular Signals Induce Axon Elongation?mentioning
confidence: 99%
“…De manière surprenante, ZPB1 se lie à la fois aux microfilaments et aux microtubules, et est capable de former des granules qui montrent des mouvements motorisés sur les deux types de structures [31]. ZBP1 peut ainsi utiliser les deux types de supports pour transporter l'ARNm de l'actine β, avec cependant des préférences cellulaires : les microfilaments dans les fibroblastes [31], et les microtubules dans les neurones [32]. Le bloquage de la localisation de l'ARNm de l'actine β à l'aide d'oligonucléotides antisens du zipcode entraîne la délocalisation de ZBP1, ce qui suggère que l'interaction ARN-protéine est essentielle au transport du complexe ribonucléoprotéique.…”
Section: Fondements Moléculaires Du Transport Des Arnm De L'actine βunclassified